Optimized VCSELs for high-power arrays - Moench, Holger; Kolb, Johanna S.; Engelhardt, Andreas P.; Gerlach, Philipp; Jaeger, Roland; Pollmann-Retsch, Jens; Weichmann, Ulrich; Witzigmann, Bernd (Proceedings of SPIE - The International Society for Optical Engineering, 2014)
High-power VCSEL systems with multi kilowatt output power require a good electro-optical efficiency at the point of operation i.e. at elevated temperature. The large number of optimization parameters can be structured in a way that separates system and assembly considerations from the minimization of electrical and optical losses in the epitaxially grown structure. Temperature dependent functions for gain parameters, internal losses and injection efficiency are derived from a fit to experimental data. The empirical description takes into account diameter dependent effects like current spreading or temperature dependent ones like voltage drops over hetero-interfaces in the DBR mirrors. By evaluating experimental measurements of the light output and voltage characteristics over a large range of temperature and diameter, wafer-characteristic parameters are extracted allowing to predict the performance of VCSELs made from this material in any array and assembly configuration. This approach has several beneficial outcomes: Firstly, it gives a general description of a VCSEL independent of its geometry, mounting and detuning, secondly, insights into the structure and the underlying physics can be gained that lead to the improvement potential of the structure and thirdly the performance of the structure in arrays and modules can be predicted. Experimental results validate the approach and demonstrate the significantly improved VCSEL efficiency and the benefit in high power systems. © 2014 SPIE.
CRIS-Team Scopus Importer:2021-06-11
Keywords: DBR losses; electro-optical optimization; High Power VCSEL System; semiconductor hetero-interfaces; VCSEL array; Vertical-Cavity Surface-Emitting Laser; wafer-characteristic parameters